Communication of Covid-19 Pandemic Disaster in Indonesia: Comunicación del desastre pandémico Covid-19 en Indonesia - RUDIANTO, B.; HENDRA, Y. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The focus of this research is to identify communication in the Covid-19 disaster response in Indonesia. It is about how the government communicates to its public. The research method is a qualitative one by analyzing some documents, books, publications, and statements made by officials. This study examined those statements in several mass media, government’s official websites, and other publication types. Besides, the printed and held policies known are made in the form of leadership commitment. The involvement of mass media in every development of the activities related to the COVID-19 disaster progress is a way of communication done by the government. RESUMEN El enfoque de la investigación es identificar la comunicación en la respuesta al desastre de Covid-19 en Indonesia. Se trata de cómo el gobierno se comunica con su público. El método de investigación es cualitativo que analiza algunos documentos, libros, publicaciones y declaraciones realizadas por funcionarios. Este estudio examinó esas declaraciones en varios medios de comunicación, sitios web oficiales del gobierno y otros tipos de publicaciones. La participación de los medios de comunicación en cada desarrollo de las actividades relacionadas con el avance del desastre del COVID-19 es una forma de comunicación que hace el gobierno.